Google Classroom Sebagai Alternatif E-Learning Pembelajaran SKI Pada Masa Pandemi Covid-19 di MA Hidayatullah - Khomisah, Soimatul; Utomo, Sigit Tri; Azizah, Ana Sofiyatul (Universitas Islam Sultan Agung, 2021)
This study discusses the application of the google classroom as an alternative to e-learning for learning SKI (Islamic Cultural History) class XII during the Covid-19 pandemic at MA Hidayatullah. This study aims to determine how the implementation of google classroom, the inhibiting factors and supporting factors as well as the solutions taken to overcome the inhibiting factors. This research is a descriptive qualitative research. The subjects of this study were students of class XII, teachers who used the google classroom application and principals of madrasah. Methods of data collection in this study using the method of observation, interviews and documentation. The data validity technique in this study used triangulation of sources and methods. The collected research data is analyzed using interactive analysis with data reduction steps, data display and verification (conclusion). Based on the results of the research, the authors can conclude that the application of the google classroom application in learning SKI class xii ma hidayatullah is going well supported by several factors, namely the ease of finding reference sources, is not bound by time and place and is easy to understand while the inhibiting factors are found is a weak signal and data quota / packet is limited. These two inhibiting factors can be overcome by providing concessions on deadlines for sending assignments and submitting online learning facilities to the relevant government. Key Word; Google Classroom, E-learning, Islamic Cultural History